Moving beyond Open Access to Digital Fluency; opportunities to create an information environment for tomorrow´s scholars - Kennedy, Mary Lee (REBIUN, 2017)
Digital Fluency is the ability to select tools, know what to do with them, explain why they work the way they do, and how scholars might adapt the digital research if the context were to change.